2019
DOI: 10.1080/02763893.2018.1534181
|View full text |Cite
|
Sign up to set email alerts
|

The Continuation of Dwelling: Safety as a Situated Effect of Multi-Actor Interactions Within Extra-Care Housing in Sweden

Abstract: This article examines the space-time situatedness of residing within extra-care housing (ECH) in Sweden. EHC constitutes an example of ordinary housing but is often categorized, along with senior housing, as "in-between housing." What differentiates the extra-care housing from the ordinary is an age limit for moving in, the provision of communal facilities, and the presence of staff at certain times each week. Two housings with different environmental and architectural conditions have been analyzed through spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Community is a subtheme connected to QOL for older people in their home environment. Socialization and social support from their community were frequently mentioned by users in several studies (Berglund-Snodgrass & Nord, 2019; Burton & Sheehan, 2010; Gobbens & van Assen, 2018; Lindahl et al, 2018; Nakhodaeezadeh et al, 2017; Orrell et al, 2013; Shin, 2018). Connection with the wider community was found to be low, whereas socialization within the community was high (Orrell et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Community is a subtheme connected to QOL for older people in their home environment. Socialization and social support from their community were frequently mentioned by users in several studies (Berglund-Snodgrass & Nord, 2019; Burton & Sheehan, 2010; Gobbens & van Assen, 2018; Lindahl et al, 2018; Nakhodaeezadeh et al, 2017; Orrell et al, 2013; Shin, 2018). Connection with the wider community was found to be low, whereas socialization within the community was high (Orrell et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al (2016) measured outdoor time and concluded that community accessibility led to increased mobility. Sense of place is highly correlated with location and spatial flexibility (Berglund-Snodgrass & Nord, 2019; Orrell et al, 2013) and is interpreted as sense of home and personal realization , which pertains to a sense of belonging and adapting to interactions with new context (Orrell et al, 2013). Sense of home is understood in relation to size, space configuration, and accessibility (Orrell et al, 2013; Van Steenwinkel et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, safety issues are important in elderly people's lives, and issues in the physical living environment of elderly people can be resolved by relevant education in the areas of facility plans, usage, and management (D'Orazio et al 2014;Fonad et al 2006;Walker et al 1992;Lina and Catharina 2019). Most of all, fire safety issues need to be addressed including not just fire prevention but also physical conditionlayout of floor and exit routes.…”
Section: Background and Purpose Of Researchmentioning
confidence: 99%